2012
DOI: 10.1038/nchembio.1002
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine assembly into toxic fibrils suggests amyloid etiology in phenylketonuria

Abstract: Phenylketonuria (PKU) is characterized by phenylalanine accumulation and progressive mental retardation caused by an unknown mechanism. We demonstrate that at pathological concentrations, phenylalanine self-assembles into fibrils with amyloid-like morphology and well-ordered electron diffraction. These assemblies are specifically recognized by antibodies, show cytotoxicity that can be neutralized by the antibodies and are present in the hippocampus of model mice and in parietal cortex brain tissue from individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
610
10
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 399 publications
(653 citation statements)
references
References 28 publications
29
610
10
4
Order By: Relevance
“…Furthermore, diphenylalanine peptides are known to form well-ordered nanotubular assemblies with amyloid-like structural signatures. 8 Adler-Abramovich et al 9 have also demonstrated that oligomers of single amino-acid phenylalanine can form well-ordered fibrillar assemblies at the nano scale. Although the prominent role of the two Phe of Ab seems to indicate that aromatic p-stacking interactions are critical for fibril formation, this has been put recently to doubt by mutagenesis experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, diphenylalanine peptides are known to form well-ordered nanotubular assemblies with amyloid-like structural signatures. 8 Adler-Abramovich et al 9 have also demonstrated that oligomers of single amino-acid phenylalanine can form well-ordered fibrillar assemblies at the nano scale. Although the prominent role of the two Phe of Ab seems to indicate that aromatic p-stacking interactions are critical for fibril formation, this has been put recently to doubt by mutagenesis experiments.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study found that the nanofibrils formed by low complexity sequences of RNA-binding proteins can recruit and retain mRNAs to form cell-free RNA granules (16), an action similar to that of TIA-1. Another study observed the assembly of phenylalanine in high concentration to form fibrils, which exhibit neurotoxicity similar to pathologic prions (17). Recent research on small molecule activators of a proenzyme also unintendedly discovered small molecules, which aggregate to form prion-like nanofibrils that selectively activate pro-caspase 3 to induce cell death (18).…”
mentioning
confidence: 99%
“…Cross-amyloid interactions could be driven by hydrophobic associations, as the presence of hydrophobic amino acids is known to yield higher amyloidal propensity (93). Most amyloid proteins display an abundance of hydrophobic residues, which could facilitate hydrophobic associations between, for example, misfolded amyloid proteins and other amyloid proteins with different sequences.…”
Section: Implications Of A␤ Cross-amyloid Interactionsmentioning
confidence: 99%